2014
DOI: 10.2478/raon-2013-0076
|View full text |Cite
|
Sign up to set email alerts
|

The influence of folate pathway polymorphisms on high-dose methotrexaterelated toxicity and survival in children with non-Hodgkin malignant lymphoma

Abstract: BackgroundWe evaluated the influence of folate pathway polymorphisms on high-dose methotrexate (HD-MTX) related toxicity in paediatric patients with T-cell non-Hodgkin lymphoma (NHL).Patients and methodsIn total, 30 NHL patients were genotyped for selected folate pathway polymorphisms.ResultsCarriers of at least one MTHFR 677T allele had significantly higher MTX area under the time-concentration curve levels at third MTX cycle (P = 0.003). These patients were also at higher odds of leucopoenia (P = 0.006) or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…Fifteen studies investigated MTHFR , with two finding no association . Nine studies found the C677T mutation in MTHFR contributed to myelotoxicity . The A1298C SNP was also associated with myelotoxicity in three studies although two studies found this polymorphism to be protective .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen studies investigated MTHFR , with two finding no association . Nine studies found the C677T mutation in MTHFR contributed to myelotoxicity . The A1298C SNP was also associated with myelotoxicity in three studies although two studies found this polymorphism to be protective .…”
Section: Resultsmentioning
confidence: 99%
“…Of the two studies investigating the gene family SLC , one study found a protective SNP, whereas the other study found an SNP associated with gastrointestinal toxicity . Additionally, both studies investigating thymidylate synthetase ( TYMS ) found an associated protective SNP …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding the clinical consequences, it is not yet possible to predict the characteristics of patients at risk for developing MTX toxicity because responses to MTX exhibit wide interpatient variability . Several pharmacogenetic studies have attempted to explain the observed interindividual variability, and a 677C>T single nucleotide polymorphism (SNP) in the methylenetetrahydrofolate reductase gene ( MTHFR ), which encodes an enzyme involved in MTX metabolism, was studied most extensively …”
Section: Introductionmentioning
confidence: 99%
“…MTHFR plays a key role in the metabolism and homeostasis of intracellular folate, and the C>T substitution in MTHFR is reported to correlate with decreased MTHFR enzyme activity, thus contributing to a low folate level . Although the genetic association of MTHFR 677C>T with MTX toxicity was evaluated in several studies, the results were conflicting …”
Section: Introductionmentioning
confidence: 99%